Pre- and post harvest factors influencing the eating quality of selected Nectarine (Prunus persica (L.) Batsch ) cultivars - Laubscher, Nicolaas Johannes (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MscAgric (Horticulture))--University of Stellenbosch, 2006.